Surrender the key - MacHale, D. J. (MacHale, D. J. Library, 2017)
In the Library between life and death, ghosts write their unfinished stories, those of their lives which ended too soon. If the reader begins reading these stories but doesn't finish them, then the stories may just finish the reader.